Identification of asymptomatic Entamoeba histolytica infection by a serological screening test: A cross-sectional study of an HIV-negative men who have sex with men cohort in Japan. - Yasuaki Yanagawa; Rieko Shimogawara; Misao Takano; Takahiro Aoki; Daisuke Mizushima; Hiroyuki Gatanaga; Yoshimi Kikuchi; Shinichi Oka; Kenji Yagita; Koji Watanabe (Public Library of Science (PLoS), 2022)
Background Amebiasis, caused by Entamoeba histolytica, is spreading in developing countries and in many developed countries as a sexually transmitted infection. Here, we evaluated the efficacy of serological screening to identify asymptomatic E. histolytica infection as a potential epidemiological control measure to limit its spread. Methodology/principal findings This cross-sectional study was carried out between January and March 2021 in an HIV-negative men who have sex with men (MSM) cohort at the National Center for Global Health and Medicine. Serological screening was performed using a commercially available ELISA kit. For seropositive individuals, we performed stool polymerase chain reaction (PCR) to determine current E. histolytica infection. We performed E. histolytica serological screening of 312 participants. None had a history of E. histolytica infection prior to the study. The overall E. histolytica seropositivity was 6.7% (21/312), which was similar to that found by the rapid plasma reagin test (17/312). We identified current infection in 8 of 20 seropositive participants (40.0%) by stool PCR. Conclusions/significance Our serological screening approach constitutes a potentially practical epidemiological strategy. Active epidemiological surveys, in combination with an effective screening strategy for asymptomatically infected individuals, should be applied to help reduce sexually transmitted E. histolytica infections.